E-contract in the Aspect of Online Sale and Purchase Agreement Correlated with Article 1320 of the Civil Code - Risma Satriana Nilamjati; Albertus Sentot Sudarwanto; Yudho Taruno Muryanto (Siber International Journal of Advanced Law (SIJAL), 2025)
When engaging in online transactions, it is highly challenging to guarantee adherence to the legal stipulations of the agreement. This challenge arises because online transactions occur via the Internet, meaning that the involved parties do not interact face-to-face, and the majority of online sales agreements are not documented in writing. The facets of "agreement" and "a specific object" will invariably be present in any online transaction, but the aspects of "skill" and "an unforeseen reason" cannot be assured. Consequently, it is essential to comply with the validity of electronic contracts in online purchasing agreements. In the author's view, this regulation represents the only legally valid approach. The goal of this article is to examine electronic contracts in the context of online sales agreements in relation to Article 1320 of the Civil Code. The methodology employed in this research is normative legal research, which investigates the legal systematics. This systematic legal examination is conducted utilizing laws and regulations or statutes pertinent to the topic being reviewed. The findings of the research indicate that the legal prerequisites of the online purchase contract are fulfilled.